Establishment of Aesthetic Soft Tissue Norms for Southern India Population: A Photogrammetric Study - Pattanaik, Snigdha; Pathuri, Sudhakar (Orthodontic Journal of Nepal, 2014)
Objective: To establish soft tissue facial profile norms for Coastal Andhra population by means of angular measurements and toevaluate the difference between male & female groups. Materials & Method: 90 individuals (45 males, 45 females) of age group 18-25 years of native coastal Andhra Pradesh, withacceptable pleasing profile, normal Class I occlusion having ideal anterior bite were selected for the study. Standard profilephotographs were taken and angular photogrammetric analysis was carried out through AutoCAD software. Result: There were significant difference in Naso-frontal angle (G–N–Nd; males: 130.64 ± 6.27o; females: 140.33o ± 6.85o; P = 0.000)and Mento-labial angle (Li–Sm–Pg: females: 127.38o ± 5.35o; males: 124.82o ± 6.57o; P = 0.043). Conclusion: The males of Coastal Andhra Pradesh have mild convex profile and prominent nose whereas females have mildconvex profile due to recessive chin. A higher upper lip prominence was seen in males. DOI: http://dx.doi.org/10.3126/ojn.v4i1.11308 Orthodontic Journal of Nepal Vol.4(1) 2014; 29-35